Quadratic BH-algebras and Quadratic TM-algebras - Shawn Adnan Bajalan; Mohammed Shahab Hassan; Aram K. Bajalan (Tikrit Journal of Pure Science, 2023)
In this paper we present the notion of “quadratic” BH-algebra and TM-algebra, and show that every quadratic BH-algebra and TM-algebra  has a product of the form    , where ; if  is a field with  and  BCI-algebra. Moreover, we show some theorems and examples with relationships among B-algebra, BH –algebra, BG-algebra and TM-algebra.